Smart Watch for Elderly Using Microcontroller with Voice Recognition - TOO MIN HUI; Mohd Hezri Mokhtar (Progress in Engineering Application and Technology, 2026)
This study focuses on the development of a simple health monitoring and alert system for basic vital signs. The main problem is that many people do not receive early warnings when heart rate or body temperature reaches unsafe levels. This issue can cause late action and increase health risks. The objective of this research is to design and test a system that can monitor heart rate and body temperature in real time and send alerts when values exceed set limits. The methodology uses sensors to measure heart rate and temperature, a microcontroller to process data, and the Blynk platform to display data and alerts on a mobile device. The system is tested under normal and abnormal conditions to check accuracy, response time, and stability. The results show that the system can detect changes in vital signs and send alerts clearly to the mobile application. The local display updates faster than the cloud display, but a small delay appears during internet transmission. Some issues such as sensor instability and connection loss occur, but troubleshooting improves performance. The study recommends improving sensor quality, network stability, and system calibration for better reliability in future use.